Study on evaluation method of young men football goalkeeper skill level - Zhang, W. (BioTechnology: An Indian Journal, 2014)
The young men football goalkeeper occupies a more important position in the football, and it also has a certain particularity. But for the evaluation method to its skill level is not very clear in our country. In the process of study, this article mainly conducts the effective analysis at each index of skill level of football goalkeeper, and it is to perform an effective exploration for the consistency of each index. At the meanwhile, it is to pay some relevant visits on experts toward the evaluation index of each skill level. After experts carry out the concrete analysis on the evaluation criterion of each evaluation index and importance, the index consistency can be fully guaranteed. Afterward, it performs an effective exploration on average score, variation coefficient of each index. In this process, combined with average score and variation coefficient criteria, it performs an effective elimination. It is for sure that evaluation index can reflect the importance of football goalkeeper skill. This second is to pursue an effective verification on validity and reliability. Through the related calculation formula, it conducts the scientific computing on the primary and secondary indexes weight. By doing so, it illustrates the reliability and validity of evaluation method in this article that can satisfy the specific requirements of the evaluation method. At last, it is to conduct the scientific construction on the evaluation system according to the point of view mentioned above, in order to make the evaluation method possible with the higher integrity. This is the main body of thought in the process of study and exploration for this article. From them, it also sufficiently display the main purpose of study for this article. Abstract by Trade Science Inc. - INDIA